The Effect of Port Site and Intra-Peritoneal Infiltration of 0.5% Bupivacaine as a Local Anesthetic on Post-Operative Analgesia in Patients Undergoing Laparoscopic Cholecystectomy under General Anesthesia - Asif, Hamna; Abbassi, Muhammad Hanif; Qureshi, Muhammad Ali Zar; Afzal, Muhammad Hamza (Biological and Clinical Sciences Research Journal, 2025)
Laparoscopic cholecystectomy (LC) is the standard surgical approach for gallbladder diseases. Despite advances in surgical techniques, post-operative pain remains a significant concern and is traditionally managed with systemic opioids, which are associated with adverse side effects. Multimodal strategies, including local anesthetic infiltration, are being explored to optimize analgesia and enhance recovery. Objective: This study aimed to evaluate the efficacy of 0.5% bupivacaine infiltration at port sites and intraperitoneally in reducing post-operative pain, opioid consumption, and enhancing early recovery after LC performed under general anesthesia. Methods: This randomized controlled trial was conducted at Combined Military Hospital, Jhelum, Pakistan, between July 2023 and December 2023. A total of 100 patients undergoing elective LC were randomly allocated to receive either port-site and intra-peritoneal infiltration of 0.5% bupivacaine (intervention group) or placebo (control group). Pain intensity was assessed using the Visual Analog Scale (VAS) at 2, 6, 12, and 24 hours postoperatively. Secondary outcomes included time to first ambulation, cumulative opioid consumption within 24 hours, and patient satisfaction using a 5-point Likert scale. Statistical analysis was performed using independent t-tests and chi-square tests, with a significance level of P < 0.05. Results: Patients in the intervention group reported significantly lower pain scores than the control group at all measured intervals (P < 0.05). At 24 hours, mean VAS scores were 2.1 ± 1.3 in the intervention group versus 4.6 ± 1.7 in controls (P = 0.002). The time to first ambulation was earlier in the intervention group (2.0 ± 0.5 hours) compared with the control group (4.0 ± 1.2 hours; P = 0.001). Total opioid use was significantly reduced in the intervention group (10.4 ± 3.2 mg) compared with controls (20.1 ± 7.8 mg; P = 0.001). Patient satisfaction scores were also higher in the intervention group (4.5 ± 0.5) compared to the control group (3.2 ± 0.8; P = 0.004). Conclusion: Infiltration of 0.5% bupivacaine at port sites and intraperitoneally provides adequate analgesia, reduces opioid requirements, accelerates mobilization, and improves patient satisfaction following LC. This approach represents a valuable adjunct to multimodal analgesia, supporting its integration into Enhanced Recovery After Surgery (ERAS) protocols.